Enhancing EFL Learning Through MyELT LMS: Evaluating the Impact of a Blended Learning Model at a Vietnamese Public University - Nguyen Giang, Binh; Tran Huu, Phuc; Tran Tin, Nghi (Forum for Linguistic Studies, 2025)
This study investigates the effectiveness of the MyELT Learning Management System (LMS) in a blended learning environment at Ho Chi Minh City University of Industry and Trade, Vietnam, targeting General English courses. It aims to enhance student performance by integrating technology with traditional teaching methods. Adopting a mixed-method approach, it analyzes academic performance records of 2,000 students, divided into MyELT users and non-users, alongside qualitative data from surveys and interviews with 200 students and 20 lecturers. Quantitative results demonstrate that MyELT users outperformed non-users, with mean process scores of 8.259 versus 7.818 and final exam scores of 7.647 versus 7.185, supported by T-tests indicating statistical significance (p < 0.001). Qualitatively, students valued the system’s flexibility and multimedia resources, while lecturers appreciated its workload reduction, though technical difficulties and the need for sustained training emerged as challenges. A notable correlation between LMS engagement and increased student interaction underscores MyELT’s role in fostering dynamic learning experiences. The study highlights the pivotal role of LMS integration in English as a Foreign Language (EFL) education, offering actionable recommendations to mitigate technical issues and enhance educator training. These improvements aim to optimize MyELT’s functionality and scalability, contributing to elevated educational quality in Vietnam and comparable settings. This research provides a robust foundation for advancing blended learning strategies in EFL contexts.